Development of Indonesian Language in Vocabulary Absorption - sulaiman, Agus; Hoon, Kim Dong (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
The purpose of this study is to analyze the process of Indonesian vocabulary development by describing the absorption of Indonesian from elements of foreign language absorption and regional languages ​​as well as languages ​​that develop in Indonesian society. Indonesian continues to develop through the process of vocabulary expansion which includes absorption from foreign languages, native languages, and also cognate languages. The data collection for this study was through the observation method with data recording techniques taken by taking representative samples of loan words originating from foreign languages. From the results of the study, foreign language loan vocabulary was obtained in KBBI which came from 4 foreign languages ​​that were adopted into Indonesian. such as Arabic, English, Greek, and Italian. Loan words originating from native languages, namely Sanskrit, and cognate loan words originating from Malay, Arabic, and Javanese. From the analysis, it shows that language expansion enriches Indonesian vocabulary without losing its original cultural identity. This phenomenon also reflects the influence of globalization, local creativity, and historical relationships between cognate languages.